Implementasi Akad Rahn Pada Pegadaian Syariah Dalam Rangka Meningkatkan Minat Masyarakat Pada Keuangan Syariah - Dayu Mirwan; Muhammad Noval; Panji Adam Agus Putra (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
Islamic financial institutions are business entities whose activities are in the field of Islamic finance and their assets, both financial and financial, are based on sharia principles. One of the Islamic financial institutions in Indonesia is the Sharia Pawnshop (Rahn). Rahn is an agreement for the delivery of goods as a form of collateral for a debt so that the person concerned may take the debt. The implementation carried out by Islamic Pawnshops includes efforts to foster Islamic financial literacy in the community, so that later the community will understand and know about Islamic Pawnshops which can help the economy in the family or create new businesses. Due to the lack of public interest in Islamic finance, especially Islamic pawnshops, the purpose of this research is to inform the concept of pawning in classical fiqh literature, the implementation of rahn contracts in Islamic pawnshops and how to increase public interest in Islamic financial institutions, especially Islamic pawn shops.